Easy Statistics : Linear and Non-Linear Regression - Buscha, Franz (Packt Publishing, 2020)
Develop linear and non-linear regression skills and gain the confidence to work with quantitative analysis About This Video Understand the statistical fundamentals of ordinary least squares (OLS) Gain the confidence to comfortably interpret complicated regression output from OLS Explore regression modeling and its application In Detail Working with statistics and quantitative reports requires a good understanding of statistics fundamentals and techniques. However, learning and applying new statistical techniques can often be a daunting experience. This is where this course comes into play. To make your experience with statistics a pleasant one, this course gives you comprehensive knowledge of basic principles of the statistical methodology, focusing on linear regression and non-linear regression. The course starts with an introduction to easy statistics and gives you an overview of the course objectives. Next, you will explore the types of regression analysis that exist and find out how ordinary least squares (OLS) works. To gain a deeper understanding of linear regression and OLS, you will learn to interpret and analyze complicated regression output from OLS. You will also focus on Gauss-Markov assumptions and zero conditional mean. Moving ahead, you will cover non-linear regression, exploring how it works, what the different non-linear regression models are, and the major uses. Towards the end, you will learn to work around with regression modeling with the help of practical examples. By the end of this video, you will be well-versed with linear and non-linear regression and the basic principles of the statistical methodology.